2020
DOI: 10.1136/openhrt-2020-001359
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on cardiology services

Abstract: ObjectiveThe COVID-19 pandemic resulted in prioritisation of National Health Service (NHS) resources to cope with the surge in infected patients. However, there have been no studies in the UK looking at the effect of the COVID-19 work pattern on the provision of cardiology services. We aimed to assess the impact of the pandemic on cardiology services and clinical activity.MethodsWe analysed key performance indicators in cardiology services in a single centre in the UK in the periods prior to and during lockdow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 8 publications
9
103
1
Order By: Relevance
“…Similar results were observed by Fersia et all. The authors observed a significant decrease in both hospital admissions and performed procedures in the Cardiology Department at Dumfries and Galloway Royal Infirmary [1]. A study by Roffi et al also showed that the COVID 19 pandemic significantly reduced the number of invasive procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were observed by Fersia et all. The authors observed a significant decrease in both hospital admissions and performed procedures in the Cardiology Department at Dumfries and Galloway Royal Infirmary [1]. A study by Roffi et al also showed that the COVID 19 pandemic significantly reduced the number of invasive procedures.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, as suggested in [ 22 ], social determinants of health such as jobs, income, may also be a factor in increased mortality from other causes. It was reported in the UK [ 23 ] that cardiovascular disease, went untreated or was less well treated during the pandemic. The CDC reported in late June that in the 10 weeks after the pandemic was declared a national emergency on 13 March 2020, hospital emergency department visits declined by 23% for heart attacks, 20% for strokes and 10% for uncontrolled high blood sugar in people with diabetes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health systems all over the world have been challenged and disrupted by soaring demand for care of COVID-19 patients. To make matters worse, factors such as fear, stigma, misinformation, and limitations on movement have bogged down the delivery of health care for a wide array of life-threatening conditions, such as cancer and cardiovascular diseases [3][4][5]. In fact, when health care systems are overwhelmed, patients may not be able to access necessary care, hence direct mortality from COVID-19 outbreaks and indirect mortality from preventable and treatable conditions both increase dramatically.…”
Section: Introduction: the Covid-19 Emergency And Termination Of Pregnancymentioning
confidence: 99%